VIRTUAL PESANTREN SEBAGAI CATALYST PENDIDIKAN ISLAM DI ERA SOCIETY 5,0 - Kusniatul Ummah, Agustiana; Hadi, Muhammad Fazlurrahman; Hayumuti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Many pesantren believe that keeping up with technological advancements in the societal era is not necessary, even though many alumni and students are not very communicative with the pesantren, creating a gap that inhibits the learning at the pesantren from being completely imparted. However, with the continuously transforming times, there will certainly be more religious issues that require experts, namely asaatidz and kiai, to adress these problems. The aim of this research is to provide an explanation of how virtual pesantren can be used as a reference strategy to enchance Islamic education in the society era, how resources are used for planning and implementation in order to maximise learning through digital technology, and the opportunities and difficulties that arise from the utilization of this strategy. This research applies the field research method, specifically using a descriptive qualitative approach. The data collection technique used is to produce accurate explanations from the observed participants through observation and interviews, which involves delivering information in the form of written or spoken words. The results found in this study indicate that the virtual pesantren as a means of enhaching Islamic education at the Ummul Quroo Islamic boarding school has a significant impact. For alumni and students who are unable to access it, the Pesantren has made a variety of social media sites available as a learning tool. In order to create high-quality pesantren, a number of digital technology components must be established, including the coordination and creation of digital platforms such as website in the Islamic education process. The conclusion that may be formed based on real information about the development of digital technology at the Ummul Quroo Islamic Boarding school, which demonstrates that the boarding school can be more proactive in producing communicative alumni using social media as an intermediary. Keywords: Virtual Pesantren, technology, Islamic Education